Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1119
|View full text |Cite
|
Sign up to set email alerts
|

How agents see things: On visual representations in an emergent language game

Abstract: There is growing interest in the language developed by agents interacting in emergentcommunication settings. Earlier studies have focused on the agents' symbol usage, rather than on their representation of visual input. In this paper, we consider the referential games of Lazaridou et al. (2017), and investigate the representations the agents develop during their evolving interaction. We find that the agents establish successful communication by inducing visual representations that almost perfectly align with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 10 publications
3
52
0
Order By: Relevance
“…Moreover, cka is known to outperform other methods such as CCA and SVCCA (Raghu et al, 2017), in identifying relationships between different layers across different architectures. While there are several other methods proposed in literature to analyze and compare representations (Kriegeskorte et al, 2008;Bouchacourt and Baroni, 2018;Chrupała and Alishahi, 2019;Chrupała, 2019), we do not intend to compare them here and instead use cka to show redundancy in the network. The mathematical definition of cka is provided in Appendix A.6 for the reader.…”
Section: Layer-level Redundancymentioning
confidence: 99%
“…Moreover, cka is known to outperform other methods such as CCA and SVCCA (Raghu et al, 2017), in identifying relationships between different layers across different architectures. While there are several other methods proposed in literature to analyze and compare representations (Kriegeskorte et al, 2008;Bouchacourt and Baroni, 2018;Chrupała and Alishahi, 2019;Chrupała, 2019), we do not intend to compare them here and instead use cka to show redundancy in the network. The mathematical definition of cka is provided in Appendix A.6 for the reader.…”
Section: Layer-level Redundancymentioning
confidence: 99%
“…Previous work that focused on the analysis of emergent languages has primarily concentrated on semantics-based analysis. In particular, they considered whether agents transmit information about categories or objects, or instead communicate using low-level feature information (Steels, 2010;Lazaridou et al, 2017;Bouchacourt and Baroni, 2018;Mihai and Hare, 2019, i.a. ).…”
Section: Related Workmentioning
confidence: 99%
“…For instance, and Havrylov and Titov (2017) showed that emergent languages can encode category-specific information through prefixing as well as wordorder and hierarchical coding, respectively. Others instead have used qualitative inspection to support the claim that messages focus on pixel information instead of concepts (Bouchacourt and Baroni, 2018), that agents consistently use certain words for specific situations (Mul et al, 2019) or re-use the same words for different property values (Lu et al, 2020), or that languages represent distinct properties of the objects (e.g. colour and shape) under specific circumstances (Kottur et al, 2017;Choi et al, 2018;Słowik et al, 2020).…”
Section: Qualitative Inspectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For such inquiries to be meaningful, the designed setup should reflect as many aspects of human communication as possible. Moreover, appropriate tools should be applied to the analysis of emergent communication, since, as several recent studies have shown, agents might succeed at a task without truly relying on their communicative channel, or by means of ad-hoc communication techniques overfitting their environment (Kottur et al, 2017;Bouchacourt and Baroni, 2018;Lowe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%